2021
DOI: 10.1038/s41398-021-01216-x
|View full text |Cite|
|
Sign up to set email alerts
|

The positive effects of running exercise on hippocampal astrocytes in a rat model of depression

Abstract: Running exercise has been shown to alleviate depressive symptoms, but the mechanism of its antidepressant effect is still unclear. Astrocytes are the predominant cell type in the brain and perform key functions vital to central nervous system (CNS) physiology. Mounting evidence suggests that changes in astrocyte number in the hippocampus are closely associated with depression. However, the effects of running exercise on astrocytes in the hippocampus of depression have not been investigated. Here, adult male ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…The hippocampus is divided into CA1, CA2, CA3, and dentate gyrus (DG). The CA1 has been reported to be linked with depression [ 23 ]. Accordingly, we chose to focus on the CA1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is divided into CA1, CA2, CA3, and dentate gyrus (DG). The CA1 has been reported to be linked with depression [ 23 ]. Accordingly, we chose to focus on the CA1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown that moderate treadmill exercise (20 min/day) for 4 weeks decreased the GFAP content in the rat hippocampus [105]. Recently, the study demonstrated that 6 weeks of running exercise significantly increased the number of GFAP+ cells and the density of BrdU+/GFAP+ cells in the hippocampal CA1 region and DG in a rat model of depression, suggesting the role of exercise to promote the generation of new astrocytes [106]. Interestingly, high levels of cleaved caspase-3 positive astrocytes were found in hippocampal CA1 and DG regions after an acute bout of exercise [107].…”
Section: The Effects Of Physical Exercise On Astrocytesmentioning
confidence: 97%
“…Further, voluntary wheel running has been shown to rescue alterations to microglia number and function in the adult cerebellum in a rodent model of Fetal Alcohol Spectrum Disorders (Gursky et al, 2020 ) and is predicted to support myelination in the adolescent brain of children with a history of prenatal alcohol exposure (Tomlinson et al, 2016 ; Wozniak et al, 2019 ). Exercise increases astrocytic coverage of blood vessels (Leardini-Tristaõ et al, 2020 ) and upregulates the number of GFAP-positive astrocytes in the HPC following ELA exposure (Belaya et al, 2020 ; Li et al, 2021 ). These astrocytic changes prevent neurodegeneration (Leardini-Tristaõ et al, 2020 ), cognitive impairment associated with Alzheimer’s disease (Belaya et al, 2020 ), depression, and lowered HPC volume (Li et al, 2021 ).…”
Section: Targeted Treatment Interventions For Ela Exposure: Preclinical and Clinical Findingsmentioning
confidence: 99%
“…Exercise increases astrocytic coverage of blood vessels (Leardini-Tristaõ et al, 2020 ) and upregulates the number of GFAP-positive astrocytes in the HPC following ELA exposure (Belaya et al, 2020 ; Li et al, 2021 ). These astrocytic changes prevent neurodegeneration (Leardini-Tristaõ et al, 2020 ), cognitive impairment associated with Alzheimer’s disease (Belaya et al, 2020 ), depression, and lowered HPC volume (Li et al, 2021 ). Microglial activation and population in HPC are reduced following exercise (Kohman et al, 2013 ; Mee-inta et al, 2019 ).…”
Section: Targeted Treatment Interventions For Ela Exposure: Preclinical and Clinical Findingsmentioning
confidence: 99%